Magneto-chemotherapy for cervical cancer treatment with camptothecin loaded Fe3O4 functionalized β-cyclodextrin nanovehicle - Rajan, Mariappan; Krishnan, Poorani; Pradeepkumar, Periyakaruppan; Jeyanthinath, Mayandi; Jeyaraj, Murugaraj; Mok, Pooi Ling; Arulselvan, Palanisamy; Higuchi, Akon; Munusamy, Murugan A.; Arumugam, Ramitha; Benelli, Giovanni; Murugan, Kadarkarai; et al. (Royal Society of Chemistry, 2017)
We portray a novel way to deal with the synthesis of iron oxide magnetic nanoparticle incorporated β-cyclodextrin (β-CD) nanocarrier stabilized by ethylenediamine tetra acetic acid (EDTA), which obtained remarkable biocompatibility and biodegradability. The functionality, crystalline nature, morphology and thermal decomposition nature of Fe3O4, β-CD–EDTA–Fe3O4 and β-CD–EDTA–Fe3O4/CPT nanocarriers were confirmed by Fourier transform infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). The mechanistic action of camptothecin (CPT) on cancer cells was studies relying to incorporation with the topoisomerase (topo I) and DNA complex formation. This prevented DNA re-ligation, causing DNA damage which resulted in apoptosis in cervical cancer (HeLa) cells. We noticed a higher number of cells arrested in the G1 phase with a decreasing cell count in the S phase and the G2/M phase at a lower concentration of β-CD–EDTA–Fe3O4/CPT. Consequently, via conjugation with Fe magnetic nanoparticles (MNPs), the molecular recognition between β-CD and target the cancerous cells make this nanovehicle a promising candidate for the non-invasive treatment of HeLa cells.